Guardians of Silence: Worklife Realities of Witness Protection Agents - Cañedo, Maricar; Sabijon, Dodelon (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study explored the work-life realities of Witness Protection Program (WPP) agents under the Witness Protection, Security and Benefit Program (WPSBP) of the Department of Justice in Cebu City, Philippines. The study aimed to examine the lived experiences, occupational challenges, coping mechanisms, and aspirations of WPP agents in the performance of their duties. Anchored on Rational Choice Theory, Social Contract Theory, and Organizational Culture Theory, the study utilized a qualitative research design employing transcendental phenomenology and Interpretive Phenomenological Analysis (IPA). Data were gathered through in-depth interviews and focus group discussions with ten actively serving WPP agents who had completed mandatory trainings and possessed at least three years of service experience. Audio recordings, field notes, and thematic analysis were used to capture and interpret the participants’ narratives and operational experiences. The findings revealed that WPP agents experience high-risk and demanding occupational conditions characterized by exposure to danger, operational pressure, media intrusion, confidentiality concerns, and multifaceted protective responsibilities. Despite these challenges, participants demonstrated resilience, adaptability, teamwork, and strong commitment to justice and public service. Emotional fulfillment derived from protecting witnesses and contributing to successful legal outcomes served as a significant source of motivation. The study also identified the importance of institutional support, professional training, healthcare benefits, and inter-agency collaboration in sustaining operational effectiveness, although budgetary limitations and public misconceptions continued to affect the efficiency of witness protection services. The study concluded that WPP agents perform a critical humanitarian and justice-oriented role in maintaining the integrity and effectiveness of witness protection operations in the Philippines. The study supports Sustainable Development Goal (SDG) 16 on Peace, Justice, and Strong Institutions through its focus on witness protection and the strengthening of criminal justice systems. It also relates to SDG 8 on Decent Work and Economic Growth by addressing workforce welfare, occupational realities, and organizational support mechanisms. The findings contribute to institutional, governance, and community sustainability by providing insights that may improve personnel welfare, operational systems, and public trust in witness protection programs.